Comparison of single-stage and two-stage thermophilic anaerobic digestion of food waste: Performance, energy balance and reaction process. (15th January 2018) - Xiao, Benyi; Qin, Yu; Wu, Jing; Chen, Hong; Yu, Panfen; Liu, Junxin; Li, Yu-You
Highlights: Two TAD of food waste both had good performances at HRT 30 d in stable stage. The VS destructions and methane yields of food waste in two TAD were comparable. Two TAD recovered similar energy from the fed and destructed food waste. Single stage TAD had higher energy recovery, rate and special rate of reaction for the four AD steps. Two-stage TAD need to be adjusted its operational parameters to improve its AD efficiency. Abstract: The single-stage and two-stage thermophilic anaerobic digestion (TAD) in lab scale continuously stirred tank reactor systems fed semi-continuously with food waste (FW) were studied to compare their performance, energy balance and reaction processes. The experimental results showed the two TADs both had good performance at a sludge retention time (SRT) of 30 d. The VS destruction (83.22 ± 1.33%) of the single-stage TAD was comparable with the two-stage TAD (82.02 ± 1.25%) during the steady period. While the average biogas yield of the two-stage TAD (0.810 ± 0.13 L/g Added VS) was higher than that of single-stage TAD (0.775 ± 0.20 L/g Added VS) and the methane content of the former (59.1 ± 1.4%) was lower than that of the latter (61.6 ± 2.1%), the methane yields of the two TADs were similar. The single stage TAD had higher energy recovery, rate and specific rate of reaction for the four AD steps than the two-stage TAD. The two-stage TAD had to adjust its operational parameters to improve its AD efficiency.